KARAKTERISTIK ENTREPRENEURSHIP DALAM ISLAM - Muhammad Ghalib; Supriadi; Mukhtar Lutfi; Hamzah Tacong (IMTIYAZ: Jurnal Ilmu Keislaman, 2026)
This study examines the concept of entrepreneurship from an Islamic perspective, including its legal foundations, characteristics, principles, attitudes, behaviors, and benefits. In Islam, entrepreneurship is not merely an economic activity aimed at generating profit but also a form of worship guided by Sharia values such as honesty, trustworthiness, justice, and social responsibility. This study aims to explain how Islam provides a normative and ethical framework for entrepreneurial activities through the Quran, Hadith, Ijma’, Qiyas, and the business practices of Prophet Muhammad (peace be upon him). The research employs a library research method with a descriptive-qualitative approach by analyzing relevant books, journals, and scholarly sources. The findings reveal that Islamic entrepreneurship is characterized by shiddiq, amanah, tabligh, fathanah, Sharia-compliant transactions, and sincere intentions of worship. Furthermore, principles such as creativity, innovation, risk-taking, hard work, and honesty serve as essential foundations for ethical business practices that contribute to both worldly prosperity and success in the hereafter.